Healthcare Provider Engagement and Its Effects on Patient Rereferral: Insights from Indonesia - Setiawan, Felicia (UI Scholars Hub, 2024)
Background: In the highly competitive landscape of healthcare, nurturing strong relationships between referring healthcare providers and healthcare facilities is essential for maintaining patient loyalty. This study explores the factors influencing referring health care provider engagement and its subsequent impact on the willingness to rerefer to healthcare facilities. Methods: A cross-sectional quantitative survey was conducted with 181 healthcare providers who regularly refer patients to a private hospital in Jakarta. Data were collected through an online structured questionnaire consisting of 29 questions. The following dimensions were covered: specialist characteristics, practice characteristics, healthcare provider–specialist interaction, patient–specialist interaction, returning referral, training opportunity, healthcare provider engagement, and willingness to rerefer to hospital. Results: The study yielded significant findings, with five out of the six antecedents associated with healthcare provider engagement demonstrating statistical significance (p < 0.05). The most significant coefficient value pertaining to healthcare provider engagement was observed in patient–specialist interaction (β = 0.287, p < 0.05). Furthermore, the analysis indicated a substantial and positive correlation between health care provider engagement and willingness to rerefer to the healthcare provider (p < 0.05). Conclusions: Healthcare providers who demonstrate engagement with the hospital are likely willing to rerefer their patients to the hospital. Therefore, to increase the willingness to rerefer patients to the hospital, hospital management should prioritize fostering engagement with healthcare providers, particularly by improving patient and specialist interaction experiences.